The First World War and health : rethinking resilience - Bergen, Leo van; Vermetten, Eric, 1961- (History of warfare, 2020)
"The First World War and Health: Rethinking Resilience considers how the First World War (1914-1918) affected mental and physical health, its treatment, and how the victims - not only soldiers and sailors, but also medics, and even society as a whole - tried to cope with the wounds sustained. The volume, which contains over twenty articles divided into four sections (military, personal, medical, and societal resilience), therefore aims to broaden the scope of resilience: resilience is more than the personal ability to cope with hardship; if society as a whole cannot cope with, or even obstructs, personal recovery, resilience is difficult to achieve. Contributors are Carol Acton, Julie Anderson, Leo van Bergen, Ana Carden-Coyne, Cédric Cotter, Dominiek Dendooven, Christine van Everbroeck, David Flecknoe, Christine Hallett, Hans-Georg Hofer, Edgar Jones, Wim Klinkert, Harold Kudler, Alexander McFarlane, Johan Meire, Heather Perry, Jane Potter, Fiona Reid, Jeffrey Reznick, Stephen Snelders, Hanneke Takken, Pieter Trogh, and Eric Vermetten"--